Improving Sixth-Grade Students' Speaking Competence through the Storytelling Method in Indonesian Language Learning - Musdalifah Ibrahim; Muhammad Aqil; Surahman Wilade; Yun Ratna Lagandesa; Muhammad Fasli (Papanda Publisher, 2026)
This classroom action research investigated the effectiveness of the storytelling method in enhancing sixth-grade students' speaking skills in Bahasa Indonesia instruction at SDN 2 Inpres Matanga, Central Sulawesi, Indonesia. The study addressed persistent challenges of limited oral expression, speaking anxiety, and teacher-centered instruction that restrict students' communicative competence development. Employing Kemmis and McTaggart's action research model, the intervention was implemented across two cycles with 20 students (8 boys, 12 girls) during September 2025. Data were collected through structured observations, speaking performance assessments, questionnaires, and documentation, analyzed using descriptive statistics and qualitative methods. Results demonstrated substantial improvements across all speaking dimensions: pronunciation increased from 60.71% to 85.71%, language use from 67.86% to 96.43%, intonation from 57.14% to 85.71%, and creativity with confidence from 62.50% to 92.86%. Overall performance advanced from 62.05% (Fair) to 90.18% (Excellent), with universal mastery achievement (100% of students) and active participation rising from 63% to 92.85%. Teacher performance improved from 90% to 100%. These findings validate storytelling as an effective pedagogical strategy grounded in constructivist, sociocultural, and communicative language teaching frameworks. The method successfully transformed passive learners into confident speakers by providing authentic communicative contexts, reducing speaking anxiety, and fostering collaborative classroom culture. This study contributes empirical evidence supporting narrative-based instruction in elementary language education and offers practical strategies for developing students' oral communication competence.